Association between body water status and acute mountain sickness. - Hannes Gatterer (Public Library of Science (PLoS), 2013)
Purpose The present study determined the association between body fluid variation and the development of acute mountain sickness (AMS) in adults. Methods Forty-three healthy participants (26 males and 17 females, age: 26 ± 6 yr, height: 174 ± 9 cm, weight: 68 ± 12 kg) were passively exposed at a FiO2 of 12.6% (simulated altitude hypoxia of 4500 m, PiO2 = 83.9 mmHg) for 12-h. AMS severity was assessed using the Lake Louise Score (LLS). Food and drink intakes were consumed ad libitum and measured; all urine was collected. Before and after the 12-h exposure, body weight and plasma osmolality were measured and whole-body bioimpedance analysis was performed. Results The overall AMS incidence was 43% (38% males, 50% females). Participants who developed AMS showed lower fluid losses (3.0 ± 0.9 vs. 4.5 ± 2.0 ml/kg/h, p = 0.002), a higher fluid retention (1.9 ± 1.5 vs. 0.6 ± 0.8 ml/kg/h, p = 0.022), greater plasma osmolality decreases (-7 ± 7 vs. -2 ± 5 mOsm/kg, p = 0.028) and a larger plasma volume expansion (11 ± 10 vs. 1 ± 15%, p = 0.041) compared to participants not developing AMS. Net water balance (fluid intake--fluid loss) and the amount of fluid loss were strong predictors whether getting sick or not (Nagelkerkes r(2) = 0.532). The LLS score was related to net water balance (r = 0.358, p = 0.018), changes in plasma osmolality (r = -0.325, p = 0.033) and sodium concentration (r = -0.305, p = 0.047). Changes in the impedance vector length were related to weight changes (r = -0.550, p<0.001), fluid intake (r = -0.533, p<0.001) and net water balance (r = -0.590, p<0.001). Conclusions Participants developing AMS within 12 hours showed a positive net water balance due to low fluid loss. Thus measures to avoid excess fluid retention are likely to reduce AMS symptoms.